Persepsi Petani Terhadap Alih Fungsi Lahan Sawah di Subak Cuculan Kota Denpasar - CHASANAH, IMROATUL; SUAMBA, I KETUT; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Farmers' Perceptions on the Transfer of Functions of Rice Land in Subak Cuculan, City of Denpasar Every year agricultural land is shrinking. In 2017-2018, Subak Cuculan experienced the largest land conversion in South Denpasar covering an area of 40ha. Rice fields are converted to non-agricultural sectors. This study aims to determine the farmers' perception of the conversion of rice fields in the Cuculan subak by making the farmers a member of the Cuculan subak as respondents. Data was collected by interview, documentation, and observation. The data that has been collected is processed using qualitative descriptive. Sampling of 30 farmers with a simple random method, the assessment uses a Likert scale to obtain valid and reliable research results. Farmers' perceptions of the conversion of paddy fields in the Cuculan subak are seen from 4 aspects. Resulting in the conclusion that farmers' perceptions of land conversion on the economic aspect scored 3.21 (neutral), the socio-cultural aspect scored 3.13 (neutral), the technical aspect got a score of 2.66 (neutral), and the environmental aspect got a score of 3.24 (neutral). Suggestions that can be given by researchers on each aspect: the economic aspect can increase the subsidy for the supply of production factors, the sociocultural aspect increases the intensity of meetings and communication, the technical aspect makes it easier to access production factors such as seeds and the environmental aspect increases the action against violations of regulations related to the disposal of factory waste.